Periodontal monitoring in orthodontic treatment with orthodontic aligners: proof of concept - Yasmin Dallarmi MIGUEL; Paola Rebelatto ALCÂNTARA; Ana Cláudia Moreira Melo TOYOFUKU; Roberto Hideo SHIMIZU (Revista de Odontologia da UNESP)
Abstract Introduction The impact of aligners in the periodontal conditions and protocols for hygiene were investigated. Objective This study assessed the periodontal condition of patients undergoing orthodontic treatment with ClearCorrect aligners and compare periodontal health conditions after the use of BlueM mouthwash and foam as clinical protocols for oral and aligner hygiene. Material and method In 16 patients’ treatment was performed using aligners, and a periodontal follow-up was conducted. The sample was divided into 3 randomized groups: Control, Mouthwash, and Foam, with each patient passing through all groups. The use of a standardized toothpaste was indicated. A periodontal examination was performed on baseline and every 2 months using gingival sulcus probing, insertion level, recession, bleeding on probe index, and biofilm presence. Result Significant differences were observed in distal probing of the teeth when comparing baseline and the mouthwash group in the intergroup analysis, irrespective of the side of the mouth and the tooth evaluated. When assessing bleeding on probe, baseline showed 1.8 times more risk of bleeding on probe than foam, 1.9 times more risk than the control, and 2.4 times more than mouthwash group. Regarding biofilm presence, baseline data showed 1.4 times more risk of having biofilm than foam, and 1.9 times more risk than mouthwash groups. In relation to the control, there was no statistically significant difference. Conclusion Patients when using BlueM mouthwash had a lower chance of bleeding on probe and presence of biofilm, as well as an improvement in distal periodontal probing depth when compared to baseline situation.